Magnesium oxide/silver nanoparticles reinforced poly(butylene succinate-co-terephthalate) biofilms for food packaging applications. (December 2021) - Zhang, Jie; Cao, Chenglin; Wang, Yibo; Xie, Lan; Li, Wei; Li, Baobi; Guo, Ruijie; Yan, Hong
Graphical abstract: Highlights: The MgO/Ag NPs were synthesized without additional reductant. PBST was first utilized in food packaging applications. The physical properties of PBST films were improved by the introduction of NPs. Synergistic antibacterial effects of MgO/Ag NPs were proved. The prepared films possess superior cherry tomato preservation properties. Abstract: Magnesium oxide (MgO)/ silver (Ag) nanoparticles (NPs) were synthesized and incorporated into poly(butylene succinate- co -terephthalate) (PBST) matrix to prepare PBST/MgO/Ag nanocomposite films by solvent casting. The effects of nanofillers on physical, antibacterial, and cherry tomato preservation properties of the PBST matrix were studied. The introduction of nanofillers effectively enhanced the thermal, mechanical, and barrier properties of the PBST matrix. Optimal properties were achieved by 3% (w/w) MgO/Ag NPs content. Their initial decomposition temperature, elongation at break, tensile strength, water vapor permeability, and oxygen transmission rate were 343.3 °C, 544.94 %, 31.57 MPa, 1.61 × 10 −11 gm/m 2 sPa, and 4.01 × 10 −11 Barrer, respectively. Owing to the enhanced antibacterial activities of the nanofillers, PBST/MgO/Ag possessed superior antibacterial activities against Gram-positive bacteria ( Staphylococcus aureus ) and Gram-negative bacteria ( Escherichia coli and Salmonella para-typhi B ). Cherry tomato preservation experiments proved the excellent preservation capability of PBST/MgO/Ag films. These findings indicated that the nanocomposites possessed potential prospects in packaging.